2008
DOI: 10.1073/pnas.0708957105
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of valanimycin biosynthesis: Elucidation of the role of seryl-tRNA

Abstract: The antibiotic valanimycin is a naturally occurring azoxy compound produced by Streptomyces viridifaciens MG456-hF10. Precursor incorporation experiments showed that valanimycin is derived from L-valine and L-serine via the intermediacy of isobutylamine and isobutylhydroxylamine. Enzymatic and genetic investigations led to the cloning and sequencing of the valanimycin biosynthetic gene cluster, which was found to contain 14 genes. A novel feature of the valanimycin biosynthetic gene cluster is the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 25 publications
2
114
0
Order By: Relevance
“…It is worth mentioning that aminoacyl-tRNAs function as donors of activated amino acids outside the protein synthesis as well (e.g., in porphyrin or phospholipid synthesis, peptidoglycan crosslinking; 30-32). Recently, it was shown that VlmL, a dedicated seryl-tRNA synthetase, and Ser-tRNA Ser participate in the biosynthesis of valanimycin, azoxy antibiotic produced by Streptomyces viridifaciens (8). Aminoacyl-CPs synthesized by aa:CP ligases may represent a substitute for aa-tRNAs as amino acid donors in such processes outside the protein biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that aminoacyl-tRNAs function as donors of activated amino acids outside the protein synthesis as well (e.g., in porphyrin or phospholipid synthesis, peptidoglycan crosslinking; 30-32). Recently, it was shown that VlmL, a dedicated seryl-tRNA synthetase, and Ser-tRNA Ser participate in the biosynthesis of valanimycin, azoxy antibiotic produced by Streptomyces viridifaciens (8). Aminoacyl-CPs synthesized by aa:CP ligases may represent a substitute for aa-tRNAs as amino acid donors in such processes outside the protein biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additional SerRSs, encoded by duplicated serS genes in two Streptomyces species, are required for antibiotic production (8) or resistance (9). These duplicated SerRSs are significantly divergent from canonical housekeeping bacterial SerRSs, but in both cases they have retained their canonical tRNA aminoacylating activity.…”
mentioning
confidence: 99%
“…The GNAT fold was recently identified in many more tRNA-dependent transferases in Streptomyces species, which utilize specific aa-tRNAs for synthesis of broad-spectrum antibiotics. For instance, the protein VlmA utilizes Ser-tRNA Ser for synthesis of the antibiotic valanimycin 45 ; DhpH and DhpK utilize Gly-tRNA Gly and Leu-tRNA Leu for biosynthesis of tripeptide phosphonate 46 ; the protein PacB utilizes Ala-tRNA Ala in the biosynthetic pathway for pacidamycin 47 ; FzmI uses Val-tRNA Val for synthesis of fosfazinomycin 48 ; Orf11 uses Gly-tRNA Gly for the synthesis of a streptothricin-related antibiotic. 49
10.1080/15476286.2017.1356980-f0003Figure 3.Role of aa-tRNA transferases exhibiting a GNAT fold.
…”
Section: The Cytosolic Domain Of Aapgs Exhibits a Gcn5-like Acetyltramentioning
confidence: 99%
“…The released nucleoside is a potent inhibitor of SerRS, so a divergent SerRS resistant to the inhibitor encoded by albomycin biosynthetic cluster protects the producer from self-poisoning . [36] On the other hand, a duplicated SerRS within the valanimycin biosynthesis cluster from Streptomyces viridifaciens apparently provides building blocks for valanimycin synthesis, since it was shown that seryl-tRNA Ser is one of the valanimycin precursors [37] and SerRS gene inactivation diminishes the antibiotic production. [38] It is noteworthy that in both examples of albomycin and valanimycin biosynthesis, duplicated SerRSs still play their aboriginal role -tRNA Ser serylation.…”
Section: Noncanonical Roles Of Serrsmentioning
confidence: 99%